PENGARUH PENGHARGAAN TERHADAP KINERJA PEGAWAI PEMASYARAKATAN DI LEMBAGA PEMASYARAKATAN KELAS IIA BINJAI - Lubis, Rezky Abadi; Rifani, Denny Nazaria (Universitas Nusa Cendana, 2024)
The purpose of this study was to examine and analyze the effect of rewards on the performance of correctional employees at the Class II A Binjai Correctional Institution. This research uses quantitative methods with a descriptive approach through primary and secondary data sources. The results showed that giving rewards to employees affected the performance of correctional employees at the Class IIA Binjai Correctional Institution. Keywords: Reward; Performance; Employee; Correctional